Neck pain in South Africa : an overview of the prevalence, assessment and management for the contemporary clinician - Rushton, Alison; Basson, Cato A.; Olivier, Benita (The South African journal of physiotherapy, 2019)
Background: Neck pain is a prevalent condition and is associated with high levels of disability and pain. The long-term prognosis can be poor, and therefore effective management in the acute stage is important. Objectives: To provide an overview of the prevalence of neck pain and physiotherapy management and to provide evidence-informed recommendations for clinical practice within a South African context. Method: The literature was reviewed considering prevalence, risk factors and examination. Management recommendations were derived from the highest levels of evidence of clinical practice guidelines, systematic reviews and randomised clinical trials. Results: Neck pain is classified into four grades, and three trajectories of recovery have been identified. Although the incidence of neck pain globally is high, in the South African context the majority of the population have limited access to physiotherapy management. Sound clinical reasoning is important in the assessment and decision-making process for management. Exercise, and mobilisation or manipulation are effective treatment options in the management of most types of neck pain. Other physical modalities such as needling, trans-cutaneous electrical nerve stimulation, laser and intermittent traction may be used as an adjunct to management. Conclusion: The burden of neck pain globally is high; however, there is a lack of information on current practice, prevalence and burden of neck pain in the South African context. Sound evidence-informed clinical reasoning to inform a working diagnosis and to enable patient-centred management is important. Clinical implications: A thorough assessment is essential to gather information to formulate hypotheses regarding diagnosis and prognosis for neck pain. Exercise, and mobilisation or manipulation are effective management options.